Formation of Hydrochlorothiazide – Para-aminobenzoic Acid Cocrystals by Solvent Evaporation Method - Haeria Doloking; Ayu Tri Sartika; Nurshalati Tahar (Universitas Islam Negeri Alauddin Makassar, 2021)
Hydrochlorothiazide is a diuretic drug used for mild to moderate hypertension were classified in Class II BSC. The purpose of this study was to explore the formation of hydrochlorothiazide-para-aminobenzoic acid cocrystal by solvent evaporation method. Cocrystals are prepared with a molar ratio of 1:0; 1:1; 1:2; and 2:1 between hydrochlorothiazide and para-aminobenzoic acid. The cocrystals were characterized by Scanning Electron Microscopy (SEM), X-ray Diffractometry (XRD), Differential Scanning Calorimetry (DSC), and Fourier Transform Infrared (FT-IR) spectrophotometer. The hydrochlorothiazide-para-aminobenzoic acid cocrystal has new crystalline peaks at 2θ of 14.904o; 15.41o; 25.553o; 26.5o; 29.844o; 31.083o indicating the formation of a new crystalline phase. The cocrystal showed the melting point at 188.57oC which is different from the initial components. The FTIR spectra of cocrystal showed the shifting of absorption peaks of groups of initial components indicating of formation of hydrochlorothiazide-para-aminobenzoic acid cocrystal through intermolecular hydrogen bond interactions between amine/sulfonamide group and carboxyl group.